Diclofenac induces basophil degranulation without increasing CD63 expression in sensitive patients - Malbrán, Alejandro (2007)
Diclofenac (Dc) induces an IgE-independent basophil (Ba) degranulation in susceptible individuals. CD63 Ba expression is utilized as an in vitro test for diagnosis of drug hypersensitivity. We tested the ability of Dc to induce CD63 Ba expression by flow cytometry (BAT) and Ba degranulation using light microscopy (HBDT) in patients sensitive to Dc. We studied 14 patients with diclofenac hypersensitivity, also two patients sensitive to Dermatophagoides pteronyssinus (Dp), and 12 normal controls. HBDT was performed by mononuclear cells toluidine blue staining. BAT determined CD63 expression in antiCD63/anti-IgE/anti-CD45-labelled whole blood. In each case, the percentage of activated Ba post-stimulation with 1 and 10 μg/ml Dc was determined. Positive controls included N-formyl-methionyl-leucyl-phenylalanine (fMLP) peptide-induced activation. IgE-mediated Ba activation was induced with a Dp allergenic extract. With Dc 1 μg/ml, mean HBDT in Dc-susceptible individuals was 33.62 ± 18.35% and 8.49 ± 4.79% in controls (P = 0.0001). Mean BAT was 2.04 ± 1.68% and 1.93 ± 1.40% in controls (P = 0.8). Ba preincubation with Dc did not affect fMLP-induced CD63 expression, neither in Dc-sensitive individuals (P = 0.8) (n = 4) nor in subjects without Dc hypersensitivity (P = 0.25) (n = 4). Ba from the two patients sensitive both to Dc and Dp responded to Dp but not to Dc by BAT: Dc, 1.99 ± 0.78%; Dp: 60.87 ± 9.28%; but showed degranulation by HBDT: Dc, 30.53 ± 1.02%, Dp: 48.78 ± 22.17%. Dc induces Ba degranulation in sensitive patients in a way that does not induce CD63 expression and is different from IgE-mediated and fMLP-mediated degranulation. Our results suggest that CD63 expression is not a reliable diagnostic method for diclofenac allergy. © 2006 The Author(s).